Evaluation and Simulation of Water Security in the Circum-Bohai Sea Region of China - Baohui Men (MDPI AG, 2021)
The function and necessity of water resources make them an important factor affecting economic and social development. To explore various water security issues impacting water use, the pressure-state-response model was applied in this study to construct a water security evaluation indexing system for the Circum-Bohai Sea Region (CBSR) in China. In this study, the game method was used to balance the two weighting methods, and the water security grades were calculated by the forward cloud model. Compared with the previous work, this study tried to analyze the simulated scenarios using the ELECTRE III method, determined the optimal development scenario mode based on the water security grade, and put forward water security measures and suggestions based on the results. This study put forward three scenarios of development models. Under the scenario of “pressure reduction”, it can be proposed to build suburbs and transfer urban functional areas to relieve the pressure of urban population. Under the “ideal state” scenario, water diversion projects and water storage projects can be proposed to relieve the regional water shortage. Under the scenario of “efficient response”, strengthening ecological environment construction and improving sewage treatment capacity can be proposed.